Konsep Nilai Sila Keadilan Sosial dalam Pendidikan Katolik - Jojor Mindo Manullang; Yakobus Ndona (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Social justice has an important role in safeguarding human rights. The Social Justice Precepts are the main objectives that form the foundation for the previous four precepts, and also become a national goal for the Indonesian nation in the formation of a state whose realization is to create a just and prosperous society based on the principles of Pancasila. Catholic education also has an important role to increase awareness of the importance of social justice in creating welfare. The method used in this study is descriptive qualitative, with the main focus on investigation through literature study. In his analysis, it was concluded that social justice has an important role in maintaining the welfare of the nation's community.